CORRELATION OF TOTAL KOLESTEROL WITH DIABETES MELLITUS TYPE 2 IN MEN - Rahayu Anggraini (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
The purpose of this study was to evaluate the correlation of total cholesterol with the incidenceof Diabetes Mellitus disease. The type of this research is observational with cross-sectional analyticapproach and done to PLN employees, total are 112 people of which are men. All participantsunderwent biochemical analysis of fasting blood sugar (BSN) and 2 hours PP (Post Prandial), andtotal cholesterol level test. Determination of glucose by glucose oxidase method and cholesterol levelby CHOD-PAP method. The mean results obtained GDP = 73 mg / dl, 2 Hours PP = 92 mg / dl innormal cholesterol patients, and in abnormal patients Cholesterol mean GDP = 81 mg / dl, 2 HoursPP = 109 mg / dl with p = 0000 in both groups of different cholesterol. Results of the Pearson'scorrelation test, there was a significant positive correlation between GDP levels and total cholesterol(r = 0.262, p = 0.005), and 2 hours PP and total cholesterol (r = 0.258, p = 0.006). Conclusions:There was a significant positive correlation between GDP levels, 2 hours PP, and total serumcholesterol. This study shows there is a correlation of total cholesterol levels that developdyslipidemia until diabetes mellitus type 2.